KAJIAN BANDINGAN ORANG - ORANG PAJANG DI KERAJAAN MATARAM ISLAM - Alifah, nFN (BALAI ARKEOLOGI PAPUA, 2010)
As Sultan Agung’s reign in the teritory of Islamic Mataram Kingdom occured Pajang’s people mobilization at the centre of the royal government. The presence of Pajang’s people in the Islamic Mataram Kingdom can be seen from politic and economic side. The Pajang Kingdom which is master in early, became gradually fell after the death of Hadiwijaya, and turned into a vassal state of Islamic Mataram Kingdom. This political condition’s change coused pros and contras among the Pajang’s people theirself. This article tries to reveal the history and background of the existence of Pajang’s people at their new place, in the centre of Islamic Mataram Kingdom government.